Catholic Church: wealth, poverty and cult of consumption - I. V. Lupandin (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2015)
The article provides an overview of the attitude of the Catholic Church to the problem of wealth and poverty, since organized in the beginning of XIII century the Catholic ascetic and reformer Francis of Assisi movement in defense of the ideals of poverty. The author considers the encyclicals of Popes Leo XIII, Benedict XV, John Paul II and Francis I, which contain theological critique of the consumer society.